Synthesis Of Banana Peel Flocculant For The Removal Of Turbidity And Bacteria Inactivation - Azamzam, Abdassalam A. (2024)
The consumption and usability of water worldwide have significantly increased in the past few years due to the surge in population. Water bodies contain huge amounts of microscopic particles and dissolved impurities, making them unfavourable for human use, especially in tropical countries. The aim of this study was to enhance the performance of banana peels bio-flocculant as one of the most common wastes in Malaysia in water treatment applications and couple it with solar disinfection process (SODIS) to disinfect the treated water.